Making economic policy in Congress - Schick, Allen (Washington : American Enterprise Institute for Public Policy Research, 1983)
This volume is the centerpiece of American Enterprise Institute work in the area of congress and economic policy. Making Economic Policy in Congress examines the role of Congress in each key area of economic affairs, from revenues and expenditures to international economics and economic forecasting. It also addresses broader questions, such as, can an incremental budget process work in an era of decrementalism? Change in economic policy making in the past decade or so and a look to the future are core elements of the book.
Includes bibliographical references and index.
hza 02/07/2018
Loans
Keywords: Economic policy; United States